ANALISIS PENDAPATAN NELAYAN PANTAI PRIGI DESA TASIKMADU KECAMATAN WATULIMO KABUPATEN TRENGGALEK - Desi Wira S (Program Studi Ekonomi Pembangunan, 2017)
Abstract This research take the title “Analysis Prigi Beach Fisherman Income Tasikmadu District Trenggalek Regency”. This research aims to determine the social economic conditional by calculating how much fisherman income and the efficiency level of Prigi Beach Fisherman Income Tasikmadu Village Watulimo District Trenggalek Regency by using quantitative descriptive analysis in order to obtain relevant data. Data collection techniques used was interviews, questioners and documentation. To know the level of gross Prigi Beach Fisherman income can be obtained by using formula TR= PxQ. Total cost is derived from sum of Total Fixed Cost with Total Variabel Cost per month (TC = FC + VC) . while net income can be calculated using the formula π = TR – TC and efficiency can be calculated by using the formula E=